KUALITAS AUDIT SEBAGAI PENENTU BIAYA HUTANG PADA PERUSAHAAN MANUFAKTUR TERDAFTAR DI BURSA EFEK INDONESIA - Robiansyah, Anton; Kamaludin, Kamaludin; Aziza, Nurna (UNIB Press, 2017)
This study aims to analyze the effect of the investment opportunity set (IOS), audit quality, debt maturity, and institutional ownership on debt costs.The population of this research is all manufacturing companies listed on the IDX in 2011-2014. The sampling technique used purposive sampling, obtained a sample of 72 companies. Data analysis used OLS (Ordinary Least Square).The results showed that audit quality has a negative effect on the cost of debt, while the investment opportunity set (IOS), debt maturity, and institutional ownership do not affect the cost of debt.